An overview of women with post-partum haemorrhage in a tertiary care centre at capital of Madhya Pradesh, India - Gadre, Sandhya; Patel, Shweta; Gadre, Abhishek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Death due to pregnancy remains an important cause of premature mortality of women worldwide. Post-Partum hemorrhage (PPH) is still most common cause of maternal morbidity and mortality. Attention needs to be paid to the prevention of PPH with organization of continuous in-service training for all the health workers to emphasize early identification of the patient’s at risk, anticipation and corresponding readiness to manage PPH cum active management of third stage of labour. Our institute is a tertiary care centre receiving moribund patients with late referral affecting the outcome adversely. This area needs to be explored methodically. The main objective is to Study the pattern of referred & in-house PPH cases, To re-emphasize the importance of antenatal supervision & anticipating, identifying and managing the complications at the earliest as well as prophylactic management of PPH, enhancing the awareness in this regard. Also to find out if there are situations where early referral to the tertiary care centre could have changed the outcome Methods: The study was conducted at Chirayu Medical College & Hospital, Bhopal, India. Retrospective data of all the cases of postpartum haemorrhage from November 2010 – October 2015, whether referred or in-house in the study period was recorded. (n= 37; 2.66%). Patients’ antenatal delivery & PPH details, management received & maternal outcome were recorded. The data was compiled & analyzed statistically in view of the aims & objectives. Results: 84 % were unbooked, 65% delivered at tertiary centre. 70% had atonic PPH, 46% PPH due to coagulopathy. 65% had severe anemia, ARF in 27%, ARDS in 19%. 65% recovered completely, 16% recovered from PPH & had some persistent morbidity, mortality 19%. Conclusions: The importance of antenatal supervised care under expert’s guidance cannot be overemphasized. Identifying the complications at the earliest can prevent many complications. Timely referral of the obstetric patients to a tertiary centre can save many lives.